Lucilius’ Orthographic Fragments: A Survey of Some Recent Works (Atti del Sodalizio Glottologico Milanese, 2021)
Lucilius’ Orthographic Fragments: A Survey of Some Recent Works. During the last two decades a remarkable Lucilius’ Renaissance has characterized the scientific approaches to the vast and multifaceted theme of Roman satire. Despite this new and impetuous stream of studies on the ancient Roman satirist from Suessa Aurunca, his renowned fragments on Latin orthography have received relatively little attention. In this paper, Chahoud’s recent work concerning Lucilius on Latin Spelling (2019), which is the only new contribution devoted to this issue in the last years, represents a good starting point to draw some overall conclusions about Lucilius’ spelling prescriptions, their theoretical background and their internal consistency.